Administrative Violations: The Origin of Sidoarjo Regional Heads' Corruption Cases: Pelanggaran Administratif: Asal-Usul Kasus Korupsi Pejabat Daerah Sidoarjo - Rahadi, Muhammad Rendy; Phahlevy, Rifqi Ridlo (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Corruption is an extraordinary crime that continually threatens national stability and public trust in Indonesia. Specific Background This systemic threat is highlighted by the recurring corruption cases in Sidoarjo Regency, where three consecutive regional heads were implicated in a short period. Knowledge Gap Current literature lacks a focused, comparative analysis of these specific Sidoarjo cases through the specialized lens of State Administrative Law (HAN) to precisely identify the administrative roots of the crimes. Aims This study employs a normative juridical method with case and statutory approaches to trace the forms of administrative violations that precede and trigger criminal acts of corruption, and to analyze the preventive role of HAN. Results Findings confirm that all three regional heads committed violations in the aspects of authority, procedure, and policy substance, establishing acts of abuse of power and neglect of legal procedures as the core problem. Novelty This research offers a unique perspective by identifying a systemic pattern of administrative deficiencies spanning three successive administrations. Implications The results necessitate the urgent application of good governance principles and the substantial strengthening of the administrative supervision system to prevent future recurrences. Highlights: Systematic administrative abuse is the core cause of corruption involving three consecutive Sidoarjo regional heads. Violations occurred in authority, procedure, and policy substance, transitioning to criminal acts. Strengthening administrative supervision and good governance principles is critical for future prevention. Keywords: Corruption, Regional Heads, State Administrative Law, Administrative Violations, Good Governance